Modos massivos e paredes de domínio em líquidos de Fermi - Brentan, Henrique Brito (Universidade Federal de São Carlos, 2018)
In this thesis, we use Fermi liquid theory to deal with three problems. The first and second problems are about a direct and an indirect detection of the amplitude massive ‘‘Higgs’’ mode in weak ferromagnets like ZrZand M nSi predicted by the ferromagnetic Landau Fermi liquid theory. The third problem is the enhanced domain wall velocities due to strong ferromagnetic fluctuations. We divided this thesis as follow: In chapter one, we did a general introduction to what this thesis deal with. In chapter two we review some topics in Fermi liquid theory necessary to understand the text ahead. In chapter three we approach the problem about the collective massive ‘‘Higgs’’ mode in weak ferromagnets and we also showed our results (dispersion relaxation and structure form factor) what can be compared with experimental results obtained from inelastic neutron scattering (a direct detection of the amplitude ‘‘Higgs’’ mode). We calculated the spectra of the collective modes in the presence of an external magnetic field and we observed that the massive amplitude ‘‘Higgs’’ mode has a 3-fold degeneracy when the spin vector wave q is not parallel either perpendicular to the external magnetic field ẑ. Still, in chapter three, we obtained a promising equation of state to the magnetization when we consider a second order phase transition theory to the energy of the ferromagnetic Fermi liquid and when we keep all second-order terms in the expansion of magnetization and in deviation of distribution function due to Fermi surface distortion. It was done to explain the Yelland observation of the decay of magnetization on weak ferromagnets like ZrZwhich it does not occur like in F e i.e. it is not a consequence of spin wave effects (magnons) and the decay of magnetization can be related to ‘‘Higgs’’. In chapter four, we introduced briefly the concept of the domain wall and we studied the dynamic of it for the situation where an induced electric current is applied to it. We assume the electric current charge carriers to behave like Fermi liquid. As consequence, we showed the domain wall velocity close to ferromagnetic critical point increases and at the same point the critical density spin current decreases.
Massive modes and domain wall in Fermi liquids
Keywords: Líquidos de Fermi; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS MAGNETICOS E PROPRIEDADES MAGNETICAS